Напрямки вдосконалення правових та організаційних засад застосування адміністративно-правового примусу органами поліції - Калашнік, В. П.; Kalashnik, V. P. (Юридична наука. - 2020. - № 3 (105). - С. 191-197, 2020)
Проаналізовано різні наукові позиції, які стосуються питання розвитку організаційних та правових засад удосконалення адміністративного примусу в діяльності поліції. Наголошено, що на сьогоднішній день як в науці, так і на офіційному державному рівні, відсутній єдиний, систематизований, вірно орієнтований погляд, який би розкривав напрями вдосконалення правових та організаційних засад застосування адміністративно-правового примусу органами поліції. В більшості випадків це питання розкривається у контексті розвитку якоїсь конкретної складової діяльності Національної поліції України, через що залишаються поза увагою ключові, індивідуальні ознаки адміністративного примусу, які дійсно потребують перероблення та переосмислення відповідно до сучасного вектору розвитку правоохоронного сектору нашої держави.

The article, based on the analysis of scientific views of scientists and current legislation, substantiates the importance and necessity of scientific research on improving the mechanism of administrative and legal coercion in the work of the National Police of Ukraine. Various scientific positions concerning the development of organizational and legal bases for improving administrative coercion in the police are analyzed. It is concluded that today, both in science and at the official state level, there is no single, systematic, well-oriented view that would reveal ways to improve the legal and organizational framework for the use of administrative and legal coercion by the police. In most cases, this issue is revealed in the context of the development of a specific component of the National Police of Ukraine, which ignores key, individual signs of administrative coercion, which really need to be reworked and rethought in accordance with the current vector of law enforcement. The directions of improvement of legal and organizational bases of application of administrativelegal coercion by the National police of Ukraine are formulated, namely: a) it is necessary to fix definition of concept of administrative coercion in the current Law of Ukraine «About national police» from 02.07.2015 № 580-VIII that to understand its essence more deeply, but also to orient more precisely legal and normative-legal regulation of the last; b) the list and interpretation of the forms of administrative and legal coercion, as well as all the methods provided by these forms and the subjects of their implementation should be clearly outlined; c) requires the gradual implementation of the institution of "presumption of justice of the police", which is to expand the guarantees of policing in the context of the use of coercive measures; strengthening legal liability for non-compliance with the requirements of police officers; improving the regulations of procedures for the implementation of coercive measures of influence; d) it is necessary to strengthen the study and use of foreign experience of administrative coercion in the police of foreign countries through the systematic involvement of representatives of the National Police of Ukraine in various seminars, conferences and other information cooperation, and to ensure the organization of such events in Ukraine to involve law enforcement authorities of foreign countries.

Проанализированы разные научные позиции, касающиеся вопроса развития организационных и правовых основ усовершенствования административного принуждения в деятельности полиции. Отмечено, что на сегодняшний день как в науке, так и на официальном государственном уровне, отсутствует единый, систематизированный, верно ориентированный взгляд, раскрывающий направления совершенствования правовых и организационных основ применения административно-правового принуждения органами полиции. В большинстве случаев этот вопрос раскрывается в контексте развития какой-то конкретной составляющей деятельности Национальной полиции Украины, из-за чего остаются без внимания ключевые, индивидуальные признаки административного принуждения, которые действительно нуждаются в переработке и переосмыслении в соответствии с современным вектором развития правоохранительного сектора нашего государства.
Directions for improving the legal and organizational framework for the use of administrative and legal coercion by the police
Калашнік, В. П. Напрямки вдосконалення правових та організаційних засад застосування адміністративно-правового примусу органами поліції / Калашнік В. П. // Юридична наука. - 2020. - № 3 (105). - С. 191-197. - DOI: https://doi.org/10.32844/2222-5374-2020-105-3.24.
Калашнік , В. П. (2020). НАПРЯМКИ ВДОСКОНАЛЕННЯ ПРАВОВИХ ТА ОРГАНІЗАЦІЙНИХ ЗАСАД ЗАСТОСУВАННЯ АДМІНІСТРАТИВНО-ПРАВОВОГО ПРИМУСУ ОРГАНАМИ ПОЛІЦІЇ. Юридична наука, (3(105), 191–197. https://doi.org/10.32844/2222-5374-2020-105-3.24.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; police; полиция; адміністративно-правовий примус; administrative and legal coercion; административно-правовое принуждение; організаційно-правові засади; organizational and legal principles; организационно-правовые основы